Contribution of Smoothened Receptor Signaling in GABAergic Neurotransmission and Chloride Homeostasis in the Developing Rodent Brain - Hamze, Mira; Medina, Igor; Delmotte, Quentin; Porcher, Christophe (Frontiers in Physiology, 2021)
In the early stages of the central nervous system growth and development, γ-aminobutyric acid (GABA) plays an instructive trophic role for key events including neurogenesis, migration, synaptogenesis, and network formation. These actions are associated with increased concentration of chloride ions in immature neurons [(Cl−)i] that determines the depolarizing strength of ion currents mediated by GABAA receptors, a ligand-gated Cl− permeable ion channel. During neuron maturation the (Cl−)i progressively decreases leading to weakening of GABA induced depolarization and enforcing GABA function as principal inhibitory neurotransmitter. A neuron restricted potassium-chloride co-transporter KCC2 is a key molecule governing Cl− extrusion and determining the resting level of (Cl−)i in developing and mature mammalian neurons. Among factors controlling the functioning of KCC2 and the maturation of inhibitory circuits, is Smoothened (Smo), the transducer in the receptor complex of the developmental protein Sonic Hedgehog (Shh). Too much or too little Shh-Smo action will have mirror effects on KCC2 stability at the neuron membrane, the GABA inhibitory strength, and ultimately on the newborn susceptibility to neurodevelopmental disorders. Both canonical and non-canonical Shh-Smo signal transduction pathways contribute to the regulation of KCC2 and GABAergic synaptic activity. In this review, we discuss the recent findings of the action of Shh-Smo signaling pathways on chloride ions homeostasis through the control of KCC2 membrane trafficking, and consequently on inhibitory neurotransmission and network activity during postnatal development.